Costs of non-small cell lung cancer in the Netherlands. (January 2016) - van der Linden, N.; Bongers, M.L.; Coupé, V.M.H.; Smit, E.F.; Groen, H.J.M.; Welling, A.; Schramel, F.M.N.H.; Uyl-de Groot, C.A.
Highlights: Mean hospital costs per NSCLC patient are €33, 143 for the entire disease duration. The estimated €33, 143 per patient is similar to other international cost estimates. These results can be used to inform health economic models. Abstract: Objectives: Real-world resource use and cost data on non-small cell lung cancer (NSCLC) are scarce. This data is needed to inform health-economic modelling to assess the impact of new diagnostic and/or treatment technologies. This study provides detailed insight into real-world medical resource use and costs of stage I-IV NSCLC in the Netherlands. Materials and methods: A random sample of patients newly diagnosed with NSCLC (2009–2011) was selected from four Dutch hospitals. Data was retrospectively collected from patient charts. This data included patient characteristics, tumour characteristics, treatment details, adverse events, survival and resource use. Resource use was multiplied by Dutch unit costs expressed in EUR 2012. Total mean costs were corrected for censoring using the Bang and Tsiatis weighted complete-case estimator. Furthermore, costs of adverse events, costs per phase of NSCLC management and costs of second opinions are presented. Results: Data was collected on 1067 patients. Total mean costs for NSCLC diagnosis, treatment and follow-up are €28, 468 during the study period and €33, 143 when corrected for censoring. Adverse events were recorded in the patient charts for 369 patients (41%) and 82 patients (9%) experienced an adverse event of grade III or higher. For these patients, adverse event-related hospital admissions cost on average €2, 091. Mean total costs are €1, 725 for the diagnostic period, €17, 296 for first treatment line, and €13, 236 for each later treatment line. Costs of providing a second opinion are €2, 580 per patient. Conclusions: Total mean hospital costs per NSCLC patient are €33, 143 for the total duration of the disease. Ignoring censoring in our data underestimates these costs by 14%. Main limitations of the study relate to the short follow-up time, staging difficulties and missing data. Its main strength is that it provides highly detailed, real-world data on the costs of NSCLC.